Analysis social feminism in the main character on the film “Layangan Putus” - Jamil, Muhammad; Hariyanto, Edy (Maliki Interdisciplinary Journal, 2023)
Analysis of social feminism in the main character on the film “Layangan Putus” is an analysis that focuses on the social struggle experienced by the main character in the film. Where the researcher uses feminism theory as a literary study in the analysis of this "Layangan Putus" film. To find the results of the data analysis, the researcher uses qualitative methods with a reading research approach. analyze the main character that describes a particular social situation by describing or explaining reality in a realistic way correct, formed by words based on data collection and analysis techniques relevant information obtained from natural situations in the form of events, phenomena or social phenomena Qualitative research is more descriptive. The data collected is in the form of words or pictures, so as not to emphasize the numbers. What results in the form of social feminism gives a big influence on the personality of a woman in fighting for her rights, the struggle in the main character reflects the social power of feminism that should be portrayed by a woman in fighting injustice.